Real-world effectiveness of ketamine in treatment-resistant depression: A systematic review & meta-analysis - Alnefeesi, Yazen; Chen-Li, David; Krane, Ella; Jawad, Muhammad Youshay; Rodrigues, Nelson B.; Ceban, Felicia; Di Vincenzo, Joshua D.; Meshkat, Shakila; Ho, Roger C.M.; Gill, Hartej; Teopiz, Kayla M.; Cao, Bing; et al. (Journal of psychiatric research, 2022)
Ketamine is a promising therapeutic option in treatment-resistant depression (TRD). The acute efficacy of ketamine in TRD has been demonstrated in replicated randomised-controlled trials (RCTs), but the generalizability of RCT data to real-world practice is limited. To this end, we conducted a systematic review (Search date: 25/12/2021; 1482 records identified) and meta-analysis of studies evaluating the real-world clinical effectiveness of ketamine in TRD patients. Four overlapping syntheses (Total n = 2665 patients; k = 79 studies) and 32 meta-regressions (Total n = 2050; k = 37) were conducted. All results suggest that the mean antidepressant effect is substantial (mean ± 95% CI, % responded = 45 ± 10%; p< 0.0001, % remitted = 30 ± 5.9%; p< 0.0001, Hedges g of symptomatological improvement = 1.44 ± 0.609; p < 0.0001), but the effect varies considerably among patients. The more treatment-resistant cases were found to remit less often (p < 0.01), but no such effect on response was evident (p > 0.05). Meta-regressions also confirmed that the therapeutic effect does not significantly decline with repeated treatments (p > 0.05). These results demonstrate that even the most treatment-resistant patients may benefit from ketamine, and that mid-to-long term treatment is effective in many patients. •This work quantifies the real-world clinical effectiveness of ketamine in a naturalistic sample of patients with treatment-resistant depression (TRD).•The clinical effectiveness of ketamine in TRD is substantial on average, but varies considerably among patient populations.•The number of failed antidepressant trials is negatively associated with stable remission, but not stable response (i.e., ≥ 50% reduction in symptomatologic score).•Several quantitative analyses converge on the conclusion that repeated ketamine treatments retain their effectiveness in many TRD cases if not most.